What do Students Think of Your Elementary Course? - Patten, Ronald J.; Steinmetz, Lawrence L. (The Accounting Review, 1966)
The article discusses a study that investigated the attitudes of accounting students towards the elementary accounting course. The authors of the study compared the effectiveness of the traditional practice set versus the business game in teaching elementary accounting principles. They conclude that there is work to be done on a continuing basis if basic accounting instruction is to improve and obtain a greater acceptance as a stimulating subject. The students are a very trying jury and yet their attitudes bear importantly on the future of accounting and accountants in terms of the image conveyed by the use of either term.